AUDITOR INDEPENDENCE IN THE VORTEX OF CONFLICT OF INTEREST: A FORTRESS OF DEFENSE OR A MERE ILLUSION OF COMPLIANCE - Rahmad Haqqi; Yusnaini Yusnaini (Jurnal Media Akademik (JMA), 2026)
Auditor independence is the cornerstone of financial reporting integrity, yet its position is frequently threatened by conflicting interests. This study aims to map how auditor independence stands as a "fortress of defense" or conversely dissolves into a mere "illusion of compliance" within a whirlpool of conflict of interest. Using a Systematic Literature Review (SLR) method on 25 global research articles from the 2021–2026 period, this study analyzes various variables affecting auditor objectivity. The mapping results indicate that independence can become a sturdy fortress when supported by personal integrity, audit staff satisfaction, and the oversight of expert audit committees. In contrast, independence tends to become an illusion when auditors are trapped by firm economic pressures, non-audit service dependence, as well as social and geographical biases. These findings provide a theoretical contribution regarding the importance of synergy between formal regulation and the strengthening of intrinsic motivation to safeguard the dignity of the auditing profession in the future.